2020
DOI: 10.1155/2020/9342732
|View full text |Cite
|
Sign up to set email alerts
|

Antitumorigenic Effects of Inhibiting Ephrin Receptor Kinase Signaling by GLPG1790 against Colorectal Cancer Cell Lines In Vitro and In Vivo

Abstract: Erythropoietin-producing hepatocellular receptors (Eph) promote the onset and sustain the progression of cancers such as colorectal cancer (CRC), in which the A2 subtype of Eph receptor expression has been shown to correlate with a poor prognosis and has been identified as a promising therapeutic target. Herein, we investigated, in vitro and in vivo, the effects of treatment with GLPG1790, a potent pan-Eph inhibitor. The small molecule has selective activity against the EphA2 isoform in human HCT116 and HCT15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…However, shifting the residues to the 4-position resulted in significantly less EPHA2 affine derivatives (15)(16)(17)(18), and by introduction of larger residues like morpholine (23) and COOEt (24) the affinities were even further reduced. In contrast to this finding, derivatives featuring the optimized disubstituted Chemistry-A European Journal phenylbenzamide substructures from Nilotinib and Ponatinib were well tolerated, showing high binding affinities towards EPHA2 (8, K D = 33 nM and 9, K D = 5 nM).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, shifting the residues to the 4-position resulted in significantly less EPHA2 affine derivatives (15)(16)(17)(18), and by introduction of larger residues like morpholine (23) and COOEt (24) the affinities were even further reduced. In contrast to this finding, derivatives featuring the optimized disubstituted Chemistry-A European Journal phenylbenzamide substructures from Nilotinib and Ponatinib were well tolerated, showing high binding affinities towards EPHA2 (8, K D = 33 nM and 9, K D = 5 nM).…”
Section: Resultsmentioning
confidence: 99%
“…Initial studies in CRC models showed promising effects of EPHA2 inhibition by small molecules. Specifically, the potent pan‐EPH inhibitor GLPG1790 was shown to selectively target EPHA2 by reducing its phosphorylation/activation in human CRC cells and inducing cell‐cycle arrest [24] . Furthermore, ALW‐II‐41‐27, a specific EPHA2 inhibitor, was shown to revert acquired resistance to the anti‐EGFR antibody Cetuximab in human CRC models [25] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As EPHA2 is a modulator of the MAPK pathway, its early inhibition may delay the development of drug resistance. Such inhibitors have already shown an antitumoral effect in vitro and in vivo in colorectal and lung cancers [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…As for other cancers [ 43 ], Eph (erythropoietin-producing hepatocellular carcinoma) receptor family members are reported as key molecules in GBM development. These receptors are primarily expressed in early development and are crucial for embryonic development and regulating processes such as cell adhesion and migration [ 44 ].…”
Section: Heterogeneity Of Human Glioblastomas and Glioblastoma Stem Cellsmentioning
confidence: 99%